2. KEJAHATAN PERANG AZOV BATTALION DALAM KONFLIK RUSIA-UKRAINA 2014: PERSPEKTIF KONSTRUKTIVIS - Faiz Fadhlurrakhman; Reni Windiani; Mohamad Rosyidin (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Russian-Ukrainian Conflict created unfortunate war crime actions led by Ukrainianvoluntary battalion, one of them was Azov Battalion. The crimes included underagemilitary recruitment, planned civilian attacks, and also torturing war prisoners. Thisresearch analyzed the war crimes of Azov Battalion using the perspective of Constructivisttheory of International Relations. The result of the research showed that Azov Battalion’swar crimes occurred due to identity factor and culture of organization. Different identitybetween pro-Ukrainian government in which Azov included inside and pro-Russianseparatist became the main reason for Azov Battalion to execute the crimes. Aside fromidentity, culture of organization which interpreting separatist as opponent while AzovBattalion in the other hand interpreted themselves as Ukrainian hero due to theirultranationalist ideology. The ideology of “The Idea of the Nation” formingultranationalist scheme to support the crime and create offensive culture in ATO operation.